Proposed Host Galaxies of Repeating Fast Radio Burst Sources Detected by CHIME/FRB - Adaeze L. Ibik; Maria R. Drout; B. M. Gaensler; Paul Scholz; Daniele Michilli; Mohit Bhardwaj; Victoria M. Kaspi; Ziggy Pleunis; Tomas Cassanelli; Amanda M. Cook; Fengqiu A. Dong; Jane F. Kaczmarek; et al. (The Astrophysical Journal, 2024)
We present a search for host galaxy associations for the third set of repeating fast radio burst (FRB) sources discovered by the CHIME/FRB Collaboration. Using the ∼1′ CHIME/FRB baseband localizations and probabilistic methods, we identify potential host galaxies of two FRBs, 20200223B and 20190110C at redshifts of 0.06024(2) and 0.12244(6), respectively. We also discuss the properties of a third marginal candidate host galaxy association for FRB 20191106C with a host redshift of 0.10775(1). The three putative host galaxies are all relatively massive, fall on the standard mass–metallicity relationship for nearby galaxies, and show evidence of ongoing star formation. They also all show signatures of being in a transitional regime, falling in the green valley , which is between the bulk of star-forming and quiescent galaxies. The plausible host galaxies identified by our analysis are consistent with the overall population of repeating and nonrepeating FRB hosts while increasing the fraction of massive and bright galaxies. Coupled with these previous host associations, we identify a possible excess of FRB repeaters whose host galaxies have M _u − M _r colors redder than the bulk of star-forming galaxies. Additional precise localizations are required to confirm this trend.